MODEL MEDIA PEMBELAJARAN DENGAN APLIKASI SMARTPHONE "AMAN" (Aplikasi Mobile Android Nyeri Persalinan) UNTUK PENINGKATAN PERSIAPAN PERSALINAN - Nining Sulistyowati; Yeti Trisnawati; Mochammad Rizki Romdoni; Misa Engelia; Marfena Amandea; Novalia Novalia (Jurnal Kebidanan, 2024)
Pain in labor is a physiological thing, but it causes a lot of fear, because it causes severe pain, sometimes even causing life-threatening physical and mental conditions. Therefore, to help the education process and make it easier for pregnant women to prepare for childbirth, the latest innovation is needed with an Android-based smartphone application to help mothers feel comfortable giving birth and a positive experience during childbirth because with a non-pharmacological method, namely eliminating pain naturally without using chemical drugs. This study aims to produce an innovation AMAN (Aplikasi Mobile Android Nyeri persalinan) that can be used for pregnant women to increase knowledge in reducing labor pain. The research method uses a research design with the ADDIE design model where the resulting product is obtained by analyzing potential problems based on literature studies and information collection; continued by designing the product; developing the product, implementing the product and evaluating the final product with the UEQ questionnaire. The results of the study showed that 6 aspects of the assessment had positive perception results. The average value calculation data shows that the stimulation aspect has the highest average value (2.18). Then followed by the brightness aspect (1.96), accuracy (1.64), novelty (1.45), and attractiveness (1.41). Meanwhile, the efficiency aspect has the lowest average value (1.09). The benchmark results obtained for the stimulation aspect are at the highest level, namely Excellent. It is concluded that the AMAN application has a positive assessment and is worthy of being developed and disseminated to the public to increase the knowledge and understanding of pregnant women in techniques for reducing labor pain